PENERAPAN MODEL CONCEPTUAL UNDERSTANDING PROCEDURES UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA DALAM PEMBELAJARAN IPA FISIKA DI KELAS VII SMPN 4 PEKANBARU - Merisa Indah Fitriani; Zuhdi Ma’aruf; Fakhruddin Z Fakhruddin Z (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to determine the increase cognitif result in physics learning of the first grade students through conceptual understanding procedures (CUPs) learning model. This research was conducted from November to December 2015 in SMPN 4 Pekanbaru with research subject is class VII10 consist of 36 students as a control group with conventional learning and class VII8 consist of 34 students as a experimental group with conceptual understanding procedures (CUPs) learning model. This research is pre-experimental with Intact Group Comparison Design. Instrument of collecting data in this research is a cognitive achievement test consisting of 15 multiple choice items. The data that collected was analyzed through descriptive and inferensial analyze. The result of descriptive analysis obtained that average absorption and effectiveness of learning in the experimental class is 84% and 73% of control class with high category and effective. The results of inferential analysis through the sign test obtained a value sig.2 tailed < 0,05 (0,00<0,05) which means Ha is accept. It show there is a significant difference between CUPs learning with conventional learning of cognitif result students of the subject matter expansion. Based on data analysis,it can be concluded that implementation of conceptual understanding procedures was able to improve the cognitive result in physics learning of the first grade students of SMPN 4 pekanbaru.Key Words: Cognitive result, Conceptual understanding procedures (CUPs) , Descriptive Analysis and Analysis Inferential